2018
DOI: 10.1002/suco.201800151
|View full text |Cite
|
Sign up to set email alerts
|

Calculation method for flexural capacity of high strain‐hardening ultra‐high performance concrete T‐beams

Abstract: In order to develop a calculation method for the ultimate flexural capacity of high strain-hardening ultra-high performance concrete (UHPC) T-beams, four-point loading tests on five specimens were carried out. The design parameters were the ratio and the strength of reinforcement. Based on the assumption of plane section, a linear regression analysis was carried out and the ultimate tensile strain of high strain-hardening UHPC was obtained. The analysis results proved that the bond between reinforcement and UH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
1
13
1
6
Order By: Relevance
“…This indicates that the tension carried by UHPC decreases as the longitudinal reinforcement ratio increases, because the tension carried by rebar increases as the longitudinal reinforcement ratio increases. By taking the relationship between the reduction factor and the longitudinal reinforcement ratio into consideration, the predictive equations for the ultimate flexural capacity of T-shaped UHPC beams were proposed, and agreed well with the experimental result in this study and previous studies [ 29 , 31 , 32 ]. The other constitutive models of UHPC, with different linearity, have not been used to verify the validity of the proposed equation in this study; this could be the objective of a future study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This indicates that the tension carried by UHPC decreases as the longitudinal reinforcement ratio increases, because the tension carried by rebar increases as the longitudinal reinforcement ratio increases. By taking the relationship between the reduction factor and the longitudinal reinforcement ratio into consideration, the predictive equations for the ultimate flexural capacity of T-shaped UHPC beams were proposed, and agreed well with the experimental result in this study and previous studies [ 29 , 31 , 32 ]. The other constitutive models of UHPC, with different linearity, have not been used to verify the validity of the proposed equation in this study; this could be the objective of a future study.…”
Section: Discussionsupporting
confidence: 86%
“…The existing experimental results about T-shaped UHPC beams [ 29 , 31 , 32 ] were employed to verify the validity of the proposed equations. The key parameters, and experimental and predicated ultimate flexural capacity of nine T-shaped UHPC beams are summarized in Table 8 .…”
Section: Theoretical Studies On Ultimate Flexural Capacitymentioning
confidence: 99%
“…The UHPC is high strain-hardening UHPC, it can work together with the reinforcement during whole loading process. 10 The uniaxial mechanical tests of UHPC, concrete and steel reinforcing bars were carried out before the shear experiments of composite beams. The experimental specimen of the UHPC uniaxial tension test was "dog bone", as shown in Figure 1.…”
Section: Materials Matrixmentioning
confidence: 99%
“…The results indicated that crack width of UHPC increased linearly with the increase of applied load until the yielding of reinforcement. Liu 18 carried out four‐point loading tests on five specimens and developed a calculation method for the ultimate flexural resistance of UHPC T‐beam. The analysis results proved that the bond between reinforcement and UHPC is reliable and they can maintain strain consistency before the reinforcement reaches its yield strength.…”
Section: Introductionmentioning
confidence: 99%